La « lucumisation » des cultes d’origine africaine à Cuba : le cas de Sagua la Grande - Silvina Testa (Journal de la Société des Américanistes)
The « lukumisation » of the religions of African origin in Cuba : the case of Sagua la Grande. Santeria or the « Lukumi religion » was born in the western part of Cuba, especially in Havana and Matanzas. After the abolition of slavery (1886) this religion spread to other parts of the island, and in so doing created a process of « lukumisation » of the other religions of African origin. This article will analyse the spread of Santeria towards the eastern part of Cuba and look specifically at the case study of Sagua La Grande.